Simulation of a continuous fluidised bed dryer for paddy - Picado, Apolinar; Gamero, Rafael (Nexo Revista Científica, 2023)
A model for simulating the drying of paddy (Oryza sativa L.) in a continuous fluidised bed dryer was employed. Equipment and material models were applied to describe the process. The equipment model was based on the differential equations obtained by applying mass and energy balances to each element of the dryer. In the case of the material model, mass and heat transfer rates in a single isolated particle were considered. Simulation results were verified by comparison with experimental data from the literature. There was a very good agreement between experimental data and simulation. The effects of gas temperature and velocity, particle diameter, dry solid flow, and solid temperature on the drying process were studied. It was found that the changes in gas velocity, dry solids flow, and solid temperature had essentially no effect on the drying process.